The Impact of Plyometric and Hurdle Jump Training on Smash Performance in the Haway Volleyball Team - Fathoni, Rachman; Manullang, Jujur Gunawan; Lestari, Hikmah (PPSDP International Journal of Education, 2024)
This study investigates the impact of plyometric and hurdle jump training on the smash performance of the Haway Volleyball Team. The methodology involved dividing team members into experimental and control groups, with the experimental group undergoing targeted plyometric and hurdle jump exercises. Baseline and post-training measurements were taken for jump height, smash speed, and accuracy. Results indicated that the experimental group showed significant improvements: a 15% increase in jump height, a 10% increase in smash speed, and a 12% increase in accuracy, while the control group showed minimal changes. These findings highlight the effectiveness of plyometric and hurdle jump training in enhancing explosive power, agility, and coordination, which are essential for successful smashes in volleyball. The discussion emphasizes the need for integrating these training methods into regular volleyball training programs to optimize player performance. Future research should explore the long-term effects and broader applications of these training interventions in different athletic contexts.